Genetic tools to study juvenile hormone action in Drosophila - A. A. Baumann (Nature Portfolio, 2017)
Abstract The insect juvenile hormone receptor is a basic helix-loop-helix (bHLH), Per-Arnt-Sim (PAS) domain protein, a novel type of hormone receptor. In higher flies like Drosophila, the ancestral receptor germ cell-expressed (gce) gene has duplicated to yield the paralog Methoprene-tolerant (Met). These paralogous receptors share redundant function during development but play unique roles in adults. Some aspects of JH function apparently require one receptor or the other. To provide a foundation for studying JH receptor function, we have recapitulated endogenous JH receptor expression with single cell resolution. Using Bacteria Artificial Chromosome (BAC) recombineering and a transgenic knock-in, we have generated a spatiotemporal expressional atlas of Met and gce throughout development. We demonstrate JH receptor expression in known JH target tissues, in which temporal expression corresponds with periods of hormone sensitivity. Larval expression largely supports the notion of functional redundancy. Furthermore, we provide the neuroanatomical distribution of JH receptors in both the larval and adult central nervous system, which will serve as a platform for future studies regarding JH action on insect behavior.